Socio-scientific issues for transforming conceptions of sexuality teaching in the training of natural science teachers - Mosquera, Jonathan Andrés; Cedeño, Elías Francisco Amórtegui; García, José Joaquín (Frontiers in Education, 2025)
IntroductionSexuality education in teacher training is often reduced to biological aspects, ignoring its affective, social, and cultural dimensions, this represents a challenge for science education and the preparation of future teachers.MethodsThis paper presents a qualitative study conducted with 28 trainee teachers of the Science Didactics program of the bachelor’s degree in Natural Sciences and Environmental Education. The objective of this research was to know the teachers’ tendencies regarding their conceptions about the nature of sexuality, its relationship with natural sciences and the affective dimension of sex education. This, before and after a didactic intervention based on the design and application of socio- scientific questions on sexuality.Results and discussionThe results show that, after the didactic intervention, the interest and willingness of teachers to be trained in sex education that includes affective, social, cultural and scientific aspects in their analysis and praxis, involving the context and favoring interdisciplinarity from the science classroom, increases.